Al-'Urf and its application in deposit products : a comparative study between Islamic and conventional banking - Bello, Shafi'i Abdul Azeez (Ahmad Ibrahim Kulliyyah of Laws,International Islamic University Malaysia, 2013)
The main purpose of the study was to explain the urf and its application in deposit products particularly under Islamic and conventional banking. This study seeks to assume that the practice of deposit products in conventional banking, which is being practiced in Islamic banking, is Shariah compliant, since the both banks operate in the same society and on the same template. First of all, it discusses the application of urf in Islamic law, particularly under the differences among urf, adah, and ijma (consensus of jurists). The proof of urf was explained critically while the legal maxims under urf and rules that govern the applicability of urf under Islamic law were also discussed. Moreover, the concept of deposit under Islamic and conventional bank were analysed effectively. The types of deposit products in both banks are chiefly current, savings accounts and investment deposits. In addition, it highlights the relationship between the depositor and the depositee, as well as the obligations of banks and account holders in current accounts and liability of entrepreneur to loss and damage in investment deposits. Furthermore, the study highlights similarities and differences between conventional and Islamic deposit products. Then it examines and analyses the model of deposit products under Islamic banking and they are represented as wadiah, qard hassan and mudarabah that are replicate of conventional banking. Furthermore, the discussion explains the issues of fatwas on deposits in Malaysia in comparison with that of the Middle East. Finally, it concludes with application of urf in Islamic and conventional banking, as well as some recommendations and some possible areas of further research.